Characteristics of white blood cell count in acute lymphoblastic leukemia: A COST LEGEND phenotype–genotype study. Issue 6 (22nd March 2022) - Helenius, Marianne; Vaitkeviciene, Goda; Abrahamsson, Jonas; Jonsson, Ólafur Gisli; Lund, Bendik; Harila‐Saari, Arja; Vettenranta, Kim; Mikkel, Sirje; Stanulla, Martin; Lopez‐Lopez, Elixabet; Waanders, Esmé; Madsen, Hans O.; et al.
Abstract: Background: White blood cell count (WBC) as a measure of extramedullary leukemic cell survival is a well‐known prognostic factor in acute lymphoblastic leukemia (ALL), but its biology, including impact of host genome variants, is poorly understood. Methods: We included patients treated with the Nordic Society of Paediatric Haematology and Oncology (NOPHO) ALL‐2008 protocol ( N = 2347, 72% were genotyped by Illumina Omni2.5exome‐8‐Bead chip) aged 1–45 years, diagnosed with B‐cell precursor (BCP‐) or T‐cell ALL (T‐ALL) to investigate the variation in WBC. Spline functions of WBC were fitted correcting for association with age across ALL subgroups of immunophenotypes and karyotypes. The residuals between spline WBC and actual WBC were used to identify WBC‐associated germline genetic variants in a genome‐wide association study (GWAS) while adjusting for age and ALL subtype associations. Results: We observed an overall inverse correlation between age and WBC, which was stronger for the selected patient subgroups of immunophenotype and karyotypes ( ρ BCP‐ALL = −.17, ρ T‐ALL = −.19; p < 3 × 10 −4 ). Spline functions fitted to age, immunophenotype, and karyotype explained WBC variation better than age alone ( ρ = .43, p << 2 × 10 −6 ). However, when the spline‐adjusted WBC residuals were used as phenotype, no GWAS significant associations were found. Based on available annotation, the top 50 genetic variants suggested effects on signal transduction, translation initiation, cell development, and proliferation. Conclusion: These results indicate that host genome variants do not strongly influence WBC across ALL subsets, and future studies of why some patients are more prone to hyperleukocytosis should be performed within specific ALL subsets that apply more complex analyses to capture potential germline variant interactions and impact on WBC.